Percutaneous auricular neuromodulation to treat pain after ambulatory breast surgery: A randomized, double-masked, sham-controlled pilot study - Brian M. Ilfeld; Wendy B. Abramson; Engy T. Said; Jacklynn F. Sztain; John J. Finneran; Jonna L. Griggs; Baharin Abdullah; Evan J. Jensen; Adam Schaar; Anne M. Wallace (Canadian Journal of Pain, 2025)
Introduction Percutaneous auricular neuromodulation involves implanting electrodes around the ear and administering an electric current. A device is currently available that is cleared to treat symptoms from opioid withdrawal, and multiple reports suggest a possible postoperative analgesic effect. This randomized, controlled pilot study aimed to (1) assess the feasibility of a postoperative auricular neuromodulation protocol and (2) provide an estimate of its treatment effects on postoperative pain and opioid consumption.Methods Adults undergoing unilateral or bilateral ambulatory breast surgery with anticipated moderate–severe pain and a single-injection paravertebral nerve block(s) received an auricular neuromodulation device (NSS-2 Bridge, Masimo) following surgery. Participants were randomized to 5 days of electrical stimulation or sham in a double-masked fashion.Results In the first 5 days, the median pain for those receiving active stimulation (n = 15) was 0 (interquartile range [IQR] = 0, 0.5] versus 1.5 (IQR = 0, 3.8) for the sham group (n = 15, P = 0.084). Concurrently, the median oxycodone use for active stimulation was 0 mg (IQR = 0, 2.5) compared to 0 mg (IQR = 0, 3) for the sham group (P = 0.905). Various secondary outcomes reached statistical significance, including maximum and average daily pain scores.Conclusions This pilot study demonstrates that percutaneous auricular neuromodulation is a feasible approach for managing pain in ambulatory surgical procedures and shows potential as an effective analgesic following discharge. Considering its ease of application, absence of systemic side effects, and lack of significant complications, conducting a definitive clinical trial seems justified because the current study was underpowered, which possibly resulted in the lack of statistical significance for the primary outcome.Registry: Clinicaltrials.gov NCT05521516.